2021
DOI: 10.3390/diagnostics11122247
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Nucleic Acid Extraction Method and the RT-qPCR Assay on SARS-CoV-2 Detection in Low-Viral Samples

Abstract: COVID-19 was initially reported in China at the end of 2019 and soon thereafter, in March 2020, the WHO declared it a pandemic. Until October 2021, over 240 million COVID-19 cases were recorded, with 4.9 mln deaths. In order to stop the spread of this disease, it is crucial to monitor and detect any infected person. The etiologic agent of COVID-19 is a novel coronavirus called SARS-CoV-2. The gold standard for the detection of the virus is the RT-qPCR method. This study evaluated two RNA extraction methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In nasopharyngeal swab samples, transported in viral transport medium and/or saline solution, Pi-Lise and QuickExtract were also efficient for nucleic acid extraction from samples with high viral load (CT ≤ 30.0) and for samples with low viral load (CT ≥ 30.0). In a study by Komiazyk et al, difficulty in extracting RNA from samples with low viral load was reported, in particular, due to operational difficulties in conventional extraction techniques (by column or organic solvents) [23]. Due to several steps in the extraction using column or solvent, and also the final eluting step in which the final concentration is dependent on the water volume added, the viral RNA concentration may be reduced, impairing the detection by RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…In nasopharyngeal swab samples, transported in viral transport medium and/or saline solution, Pi-Lise and QuickExtract were also efficient for nucleic acid extraction from samples with high viral load (CT ≤ 30.0) and for samples with low viral load (CT ≥ 30.0). In a study by Komiazyk et al, difficulty in extracting RNA from samples with low viral load was reported, in particular, due to operational difficulties in conventional extraction techniques (by column or organic solvents) [23]. Due to several steps in the extraction using column or solvent, and also the final eluting step in which the final concentration is dependent on the water volume added, the viral RNA concentration may be reduced, impairing the detection by RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, a new, faster technique of nucleic acid extraction was compared to the “reference” method, which represents the evolution. As already reported in the literature, the impact of RNA extraction is fundamental in SARS-CoV-2 detection [ 18 , 19 ] and, on the contrary, in diagnostics, the data about time consumption are also very important [ 20 ]. In fact, other papers have already demonstrated that performing a combination of rapid and quality RNA isolation is possible [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Komiazyk et al showed that the lower the viral load, the more difficult it is to interpret the results. This appears to be due to problems with available diagnostic tests failing this low viral load, which is still capable of infection [ 18 ]. With CT ≥ 35, the test also reacts with some portion of the virus, while the virus itself is no longer present; therefore, the subject is no longer contagious.…”
Section: Discussionmentioning
confidence: 99%
“…Virus RNA acids were isolated using two procedures, column-based extraction by Viral DNA/RNA kit (A&A Biotechnology, Gdansk, Poland) and magnetic-based method via NucleoMag Pathogen kit (Machery-Nagel, Duren, Germany) with modifications to the manufacturers’ instructions, as described previously [ 45 ].…”
Section: Methodsmentioning
confidence: 99%